Genital prolapse - pathogenesis and clinical. - Díaz H., Víctor (2015)
547 patients diagnosed with Genital Prolapse admitted to the Gynecology Department of Obstetrics and Gynecology Hospital "Arzobispo Loayza" during the years 1971-1973 are studied. The pathogenesis of genital prolapse is studied considering the 3 main factors: congenital weakness of the development of the media, injuries during delivery and atrophy of the supporting tissues in the climacteric. The frequency of this condition in the Service is 37.9%. The age distribution ranges ranges from 26 years for retail and 81 years for most, with an average of 53 years. With respect to the average of births / woman was 6.27, which shows the importance, multiparity in the pathogenesis of this condition. It discusses and gives statistical information regarding their grouping according to their development levels being the highest number of injury cases has the Cystocele with 92.5%, followed by Rectocele 57.9% and 26.1% hysterocele.